Analisis Tanda dan Simbol pada Ekosistem serta Proses Belajar di SMAN 14 Medan tentang Penghargaan dan Penghayatan Identitas Bangsa Indonesia - Tiara Laura Br Ginting; Liesna Andriany (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to analyze how the appreciation and application of Indonesian national identity at SMAN 14 Medan on symbols and signs that exist in the school ecosystem and the learning process. The type of research used is qualitative research and the methods used are case study and observation methods. The results of the analysis show that there are several signs and symbols related to the identity of the Indonesian nation both of symbols that are visible in real terms or have visualization, as well as in appreciation of values through behavior and actions, especially symbols and signs related to the Indonesian nation identity in the form of Pancasila and diversity. Symbols and signs related to values of diversity is application of Indonesian language and no discrimination, agent of change team, anti bullying posters in school environment. Symbols and signs related to Pancasila values is there are religious activities, application of 5S everymorning, flag ceremony, group assignment in class, and friday clean.